2007
DOI: 10.1038/sj.ijo.0803746
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of dietary energy density at age 5 and 7 years and fatness at 9 years among UK children

Abstract: Objective: To analyse whether high dietary energy density (DED) is associated with increased fat mass and risk of excess adiposity in free-living children. Design: Longitudinal, observational cohort study. Subjects: Six hundred and eighty-two healthy children from the Avon Longitudinal Study of Parents and Children. Measurements: Diet was assessed at age 5 and 7 years using 3-day diet diaries, and DED (kJ g À1 ) was calculated excluding drinks. Fat mass was estimated at age 9 years using Dual-Energy X-ray Abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 42 publications
3
113
1
1
Order By: Relevance
“…These foods may reflect home cooking as well as fast food consumption and hence the association with diet quality may not be as straightforward. The mean energy density values in our study are slightly lower than those published by Johnson et al (2008a) and McCaffrey et al (2008), but their dietary assessment methods differed from ours and their subjects were younger. Mendoza et al (2006) reported much lower values but did not exclude all beverages in their calculations.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These foods may reflect home cooking as well as fast food consumption and hence the association with diet quality may not be as straightforward. The mean energy density values in our study are slightly lower than those published by Johnson et al (2008a) and McCaffrey et al (2008), but their dietary assessment methods differed from ours and their subjects were younger. Mendoza et al (2006) reported much lower values but did not exclude all beverages in their calculations.…”
Section: Discussioncontrasting
confidence: 54%
“…To the best of our knowledge, no other studies comprehensively describing dietary quality and energy density in children under free-living conditions have been published, although Johnson et al (2008a) did report a relationship between dietary energy density and percent energy from total fat (positive) and fibre (negative) in a sample of UK children. A cross-sectional association between energy density and selected predictors of obesity (Mendoza et al, 2006), and a longitudinal association with overweight (McCaffrey et al, 2008;Johnson et al, 2008a), have also been reported in children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The evidence for the association in young people was based on four methodologically rigorous longitudinal studies, whose key strengths were: (1) use of objective measures of adiposity (including dual-energy X-ray absorptiometry or doubly-labelled water) rather than reliance on proxy measures such as BMI; (2) mis-reporting of dietary EI was appropriately adjusted for; (3) ED was calculated by recommended methods that excluded all or most beverages, to avoid attenuation of results (62)(63)(64)(65) . The latter issue is of critical importance in evaluating associations between ED and adiposity (65) .…”
Section: Observational Evidencementioning
confidence: 99%
“…It is important to make adjustments for possible misreporting of intakes when using dietary data. In ALSPAC, several methods of assessment of misreporting and subsequent adjustment have been used Johnson et al, 2007).…”
Section: Misreporting Of Dietary Intake and Energy Adjustmentmentioning
confidence: 99%